The Effects of Syria War on Turkey-EU Relations - Sambur, Bilal (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
Syrian war has changed Middle East radically. Regional dynamics and actors have deeply influenced by Syrian war. Turkey is one of the Middle Eastern countries, which has influenced from this conflict most. Turkey has close relations with the EU in order to become its full member. Syrian war caused many problems between Turkey and the EU. Refugee crisis, Idlib problem, military interventions of Turkey in Syria and Eastern Mediteraanian disputes are chief problemler between Turkey and the EU. Syrian war brings Turkey and the EU relations to the end. In this paper, we intend to discuss the effects of Syria war on Turkey-the EU relations.

Wojna syryjska radykalnie zmieniła Bliski Wschód. Dynamika regionalna i aktorzy wywarli głęboki wpływ na wojnę w Syrii. Turcja jest jednym z krajów Bliskiego Wschodu, które najbardziej wywarły wpływ na ten konflikt. Turcja utrzymuje bliskie stosunki z UE, aby stać się jej pełnoprawnym członkiem. Wojna syryjska spowodowała wiele problemów między Turcją a UE. Kryzys uchodźczy, interwencje wojskowe Turcji w Syrii i spory wschodniośródziemnomorskie są głównymi problemami między Turcją a UE. Wojna w Syrii kładzie kres stosunkom Turcji i UE. W niniejszym artykule autor zamierza omówić skutki wojny w Syrii dla relacji Turcja-UE.
Wpływ wojny w Syrii na stosunki Turcja-UE
Keywords: Syria; refugee; membership; border; Syria; uchodźca; członkostwo; granica